Overcoming Barriers to Prescribing Buprenorphine for the Treatment of Opioid Use Disorder: Recommendations from Rural Physicians. Issue 1 (19th October 2018) - Andrilla, C. Holly A.; Moore, Tessa E.; Patterson, Davis G.
Abstract: Purpose: The United States is in the midst of a severe opioid use disorder epidemic. Buprenorphine is an effective office‐based treatment that can be prescribed by physicians, nurse practitioners, and physician assistants with a Drug Enforcement Administration (DEA) waiver. However, many providers report barriers that keep them from either getting a DEA waiver or fully using it. The study team interviewed rural physicians successfully prescribing buprenorphine to identify strategies for overcoming commonly cited barriers for providing this service. Methods: Interview candidates were randomly selected from a list of rurally located physicians with a DEA waiver to prescribe buprenorphine who reported treating high numbers of patients on a 2016 survey. Forty‐three rural physicians, who were prescribing buprenorphine to a high number of patients, were interviewed about how they overcame prescribing barriers previously identified in that survey. Findings: Interviewed physicians reported numerous ways to overcome common barriers to providing buprenorphine treatment in rural areas. Key recommendations included ways to (1) get started and maintain medication‐assisted treatment, (2) minimize DEA intrusion and medication diversion, and (3) address the lack of mental health providers and stigma surrounding opioid use disorder (OUD). Overall, physicians found providing this service to be very rewarding. Conclusions: Despite known barriers, rural physicians around the country have been successful in adding buprenorphine treatment to their practices. Nonprescribing providers can learn from the strategies used by successful prescribers to add this service.